Estimation of biosorption characteristics of chromium (VI) from aqueous and real tannery effluents by treated T. vulgaris: experimental assessment and statistical modelling. Issue 16 (16th December 2022) - Boddu, Sumalatha; Alugunulla, Venkata Narayana; Dulla, John Babu; Chavali, Murthy; Pilli, Rajasekhar Reddy; Khan, Anoar Ali
ABSTRACT: The current study has focused on the removal proficiency of acid-treated brown marine algae Turbinaria vulgaris ( T. vulgaris) for the removal of Cr (VI) from laboratory grade solution along with real tannery effluent. Surface morphology, elemental configuration, structural parameters and functional group identification of the acid-treated T. vulgaris were done through appropriate analysis. The optimized ranges of significant components for biosorption study were initial Cr (VI) ion concentration (20–100 mg.l −1 ), pH (1–3), biosorbent concentration (0.1–0.5 g.l −1 ) and temperature (283–323 K). The maximum removal percentage (90.08%) of Cr (VI) through biosorption by T. vulgaris is achieved at optimum conditions: pH 2.39, initial metal ion strength-19.85 mg.l −1, biosorbent quantity-0.26 g.l −1 and temperature-299.44 K. Characterisation of T. vulgaris was done before and after sorption study. The removal characteristics were validated through different isotherms and kinetic models towards the estimation of solute interaction and biosorption nature. The entire experimental results concluded that biosorption of Cr (VI) obeys pseudo second-order kinetics. Biosorption of Cr (VI) onto T. vulgaris follows Freundlich isotherm ( R 2 = 0.999), with maximum removal capability of 21.25 mg.g −1 . Thus, acid-treated T. vulgaris could be an efficient biosorbent towards the removal of Cr (VI) from chromium containing waste effluent. Graphical Abstract: uf0001